Professors Public Lecture share expertise in the Innovation of Specialty Chemicals and Graphene - Naqiah, Puaad (UMPSA, 2024)
GAMBANG, 4 April 2024 - The Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Professors' Public Lecture provided an opportunity for academics to share their expertise and enrich knowledge with intellectual thinking related to contemporary issues and societal culture in this country.